P268 Development and validation of a novel composite index for the assessment of endoscopic and histologic disease activity in pouchitis: The Atlantic pouchitis index. (30th January 2023) - Sedano, R; Ma, C; Hogan, M; Silverberg, M S; Zou, G; D'Haens, G R; Rémillard, J; Mcfarlane, S C; Bojic, B; Bressler, B; Rosenfeld, G; Feakins, R M; et al.
Abstract: Background: Several instruments have been used in clinical trials of pouchitis to define eligibility criteria and outcome measures but have not been formally validated. A need remains for a validated pouchitis instrument that is suitable for use in novel drug development. We developed and internally validated the novel composite Atlantic pouchitis index (API) for the assessment of endoscopic and histologic disease activity in patients with pouchitis. Methods: Paired baseline and week 10 endoscopic videos and histologic images were obtained from 98 patients with chronic antibiotic-refractory pouchitis who participated in a randomised placebo-controlled trial of alicaforsen enema (ClinicalTrials.gov identifier: NCT02525523). For each pair, 4 endoscopists and 3 pathologists scored 59 items. These items included 51 component items from 11 indices (4 endoscopic, 4 histologic, 3 composite) identified in a prior systematic review and 8 additional items identified in a prior Research and Development/University of California Los Angeles appropriateness methodology exercise. The reliability of all measures was assessed using intraclass correlation coefficients (ICCs) and interpreted according to Landis and Koch benchmarks (slight, 0.00-0.20; fair, 0.21-0.40; moderate, 0.41-0.60; substantial, 0.61-0.80; almost perfect, 0.81-1.00). Responsiveness was evaluated using the area under the receiver operating characteristic curve (AUC). The API was developed using linear regression with a 100-mm visual analogue scale (VAS) of pouchitis activity as an anchor. Results: Among all measures assessed for reliability and responsiveness, the simple endoscopic score for Crohn's disease (SES-CD) and the Robarts histopathology index (RHI) were selected for inclusion in the API. The total API score ranges from 0 to 69, with higher scores indicating more severe disease activity, and can be calculated as API = (3 × SES-CD [0 to 12]) + (1 × RHI [0 to 33]). The API demonstrated almost perfect intra-rater reliability (ICC, 0.88 [95% CI: 0.81, 0.92]), substantial inter-rater reliability (ICC, 0.72 [95% CI: 0.60, 0.79]), and a high correlation with the VAS (r = 0.84 [95% CI: 0.76, 0.89]). Index responsiveness in detecting meaningful improvements in disease activity was higher for the API (AUC, 0.95 [95% CI: 0.89, 0.98]) than for existing endoscopic indices (∆AUC, 0.09-0.24; P ≤0.005) (Table). Conclusion: The novel API is a composite index of endoscopic (SES-CD) and histologic disease activity (RHI) that is reliable and significantly more responsive than existing endoscopic pouchitis scoring systems. The API is a promising tool for use in clinical trials of novel therapies for pouchitis. Further validation is needed in independent datasets.